Surface electromyographic wheel speed skate protocol and its potential in athletes` performance analysis and injury prevention - Bongiorno, G.; Sisti, G.; Dal Mas, F.; Biancuzzi, H.; Bortolan, L.; Paolatto, I.; Rosa, M.; Miceli, L. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Speed skating is a discipline that involves cyclical and repetitive movements that make athletes susceptible to injuries, especially in the groin. In professional athletes, during a season, it was found that about 20% had overuse injuries with significant consequences during the competitive season due to long recovery times. Currently, new technological tools allow the measurement of multiple parameters and, through a panel of data deriving from various measurements, provide a valuable aid for training and rehabilitative purposes. This study aimed to probe the potential of the new analysis algorithm, or its ability to detect differences in electromyographic and acceleration patterns between newcomers to the discipline and professional athletes. METHODS: We proceeded through measurements using a system based on an inertial sensor and four probes for surface electromyography. RESULTS: The analysis highlights important differences both from the point of view of accelerations (with marked oscillations on the three axes of the neophyte concerning greater stability of the professional`s trunk) and a different pattern of muscle activation during joint movement a greater coactivation of the neophyte compared to the professional, which could lead to a greater risk of injury due to less training. CONCLUSIONS: This new protocol, when validated on a statistically significant sample of elite athletes leading to specific benchmarks, can be used to improve athletes` performances and maybe to prevent athletes` injuries.